Character Education Management: A Case Study of the Role of Teachers in High Schools - Alifya Nurzehan; Endang Herawan; Nurdin; Sururi; Diding Nurdin (Didaktika: Jurnal Kependidikan, 2024)
This study aims to identify and analyze the role of teachers in shaping character education management in Senior High Schools (SMA). Character education is a top priority in shaping students' personalities and morals, and teachers play a central role in its implementation. Using qualitative methods with a case study approach in several selected high schools, this study found that teachers not only act as learning facilitators, but also as the main agents in instilling character values ​​such as honesty, responsibility, and discipline. However, the implementation of character education in high schools faces several challenges, including the lack of special training for teachers, minimal support facilities, and inconsistent school policies in integrating character education. Therefore, strong support from school management and the involvement of parents and the community are important factors in the success of the implementation of character education. Based on the research results, it is recommended that there be ongoing training for teachers and increased synergy between schools, families, and the environment in supporting character education.